Educação musical e autismo: a contribuição da música no desenvolvimento da interação social de crianças com Transtorno do Espectro Autista (TEA) - Ferri, Álvaro Nery (2023)
This dissertation, linked to the research line Educational Processes and Language, of the Postgraduate Program in Education at the University of Passo Fundo/RS, sought to answer the following question: What possibilities can Carl Orff's musical methodology provide for the development of social interaction, as advocated by Vygotsky, in subjects with Autism Spectrum Disorder (ASD)? To this end, the research was based mainly on the conceptions of two authors. These are the Belarusian psychologist Lev Vygotsky, known for establishing cultural-historical psychology, and the German Carl Orff, a music educator who made a major contribution to the field of music pedagogy through his Orff method, emphasizing the importance of collective music-making. In this context, we sought to understand how Music Education can contribute to the social interaction of individuals, given that one of the main characteristics present in this spectrum is the difficulty in this regard. In terms of specific objectives, the aim was to: a) develop a historical overview of the origins and concepts of Music Education; b) draw on the theoretical backing of Lev Vygotsky and Carl Orff; c) carry out a detailed review of autism, as well as studies related to this spectrum; d) organize and implement a didactic sequence based on the authors guiding the research; e) analyze the extent to which Carl Orf's musical methodology supports the development of social interaction in individuals on the autistic spectrum. Based on these objectives, a qualitative research-intervention was carried out, based on Trivinõs (1987) and linked to Autism Spectrum Disorder (ASD). Data collection was based on the researcher's logbook entries, photos and video recordings of the meetings. The data was then examined using Content Analysis, using the following categories, defined a posteriori: analysis of group interaction, analysis of understanding of the activities and analysis of the structure of the didactic sequence. The results showed that the musical methodology developed by Carl Orff helps develop social interaction in people with Autism Spectrum Disorder (ASD). This conclusion resulted from the fact that the concept of elementary music developed by the author, taking into account observation, imitation and appropriation, enables different experiences and forms of learning for people with ASD and, consequently, favors social interaction in groups